2017
DOI: 10.1177/0972150916668606
|View full text |Cite
|
Sign up to set email alerts
|

Equity Concentration, Agency Costs and Performance of Non-financial Firms Listed on the Saudi Stock Exchange (Tadawul)

Abstract: This article examines the association between the equity concentration and agency costs as well as the impact of agency costs on performance of non-financial firms listed on the Saudi Stock Exchange (Tadawul). These relations are examined by using dynamic panel data and a two-step robust system estimation for the period 2010–2013. The study uses three proxy variables to measure agency costs. The results show that the equity concentration has no significant impact on agency costs, and the agency costs have no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…There are many empirical investigations have been conducted and mostly in the developed countries (Antoniadis et al, 2008;Migunyi, Zanjirder and Gasemy, 2013;Wambua, 2013;Nobance, Ellili and Abraham, 2017;Hau, 2017;Kadiugloe et al,2017;Abdullah et al, 2019). According to Jensen's (1986) theory, having a big free cash flow might lead to a conflict within the company, such as between the interest manager and the shareholder, which will harm the company's performance.…”
Section: Free Cash Flow Agency Cost and Firm Performancementioning
confidence: 99%
“…There are many empirical investigations have been conducted and mostly in the developed countries (Antoniadis et al, 2008;Migunyi, Zanjirder and Gasemy, 2013;Wambua, 2013;Nobance, Ellili and Abraham, 2017;Hau, 2017;Kadiugloe et al,2017;Abdullah et al, 2019). According to Jensen's (1986) theory, having a big free cash flow might lead to a conflict within the company, such as between the interest manager and the shareholder, which will harm the company's performance.…”
Section: Free Cash Flow Agency Cost and Firm Performancementioning
confidence: 99%
“…Whereas Blockholding and agency cost Ang et al (2000) and Florackis and Ozkan (2008) found a significant negative blockholdingagency cost relationship, Truong and Heaney (2013) found a positive relationship. Nobanee et al (2017) and Singh and Davidson (2003) reported a nonsignificant relationship. Engelen (2015) found that the relationship depends on the measure of agency cost and blockholder identity.…”
Section: Blockholding-agency Cost Relationshipmentioning
confidence: 82%
“…Urban (2015) obtained similar results with lagged independent variables, which according to him, provides evidence inconsistent with the idea of simultaneity in the blockholding-agency cost relationship or because blockholding remains relatively stable over time (Donelli et al, 2013;Urban, 2015). Some authors have addressed simultaneity concerns through instrumental variable-based techniques such as the two-stage least squares and generalized method of moments that also use lagged variables of predictors (see Nobanee et al, 2017). However, as some authors have pointed out, lagged values of predictors hardly solve reverse causality concerns (Edmans and Holderness, 2017;Reed, 2015).…”
Section: Blockholdingmentioning
confidence: 99%
See 2 more Smart Citations